The therapeutic alliance as an indicator of well-implemented and impactful employee counseling services: Deployment of the Brief Therapeutic Alliance Scale in an employee assistance program. (2nd January 2023) - Milot, Marc
Abstract: An implementation fidelity study evaluated the quality of the therapeutic alliance (TA) in the counseling services of a Canadian Employee Assistance Program (EAP). The aims were to evaluate the level of TA experienced by EAP users during counseling, to assess the influence of client gender, and to determine the associations between the level of TA and mental health and work functioning outcomes. The TA was assessed with the Brief Therapeutic Alliance Scale (BTAS-5), a self-report quantitative measure developed to rapidly assess multiple elements of the client-therapist alliance from the perspective of the client. The majority of the EAP users ( N = 1277) reported experiencing a high level of TA during counseling and men and women reported equal levels. Pretest and posttest analysis with ANCOVA showed that EAP users ( N = 505) reporting higher levels of TA had greater mental well-being, lower depression symptoms (Patient Health Questionnaire-2), lower work presenteeism (Workplace Outcome Suite-5; WOS-5), and greater life satisfaction (WOS-5) at follow-up after end of counseling. The TA from the perspective of EAP users can serve as an indicator of well-implemented employee counseling services and its assessment can provide additional evidence of counseling quality and effectiveness, supplementing the findings of traditional outcomes-based EAP studies.